PERLINDUNGAN HUKUM BAGI PENYANDANG DISABILITAS UNTUK MEMPEROLEH PERSAMAAN HAK DIDALAM PEMERINTAHAN - Muhamad Arganata (Legal Spirit, 2019)
Legal Protection for Persons with Disabilities to Obtain Rights Equations in Government, the existence of Discrimination in Article 65 paragraph (1) letter b of Law Number 5 of 2014 concerning State Civil Apparatus which requires prospective ASN to be physically and mentally healthy. Of course we know that there are humans who are less than perfect or called Disabled Persons. Therefore, with this regulation, people with disabilities feel discrimination because they will not be able to meet the requirements of physical and spiritual health even though in fact they have the same abilities and opportunities (Article 28I paragraph (2) of the 1945 Constitution of the Republic of Indonesia) with normal human beings , only they have differentneeds. Efforts to Improve Legal Protection for Persons with Disabilities, as follows: Ensure and implement the importance of political education (civic education) for persons with disabilities in formal education institutions, Make changes to the contents of article No. 5 of 2014 concerning State Civil Apparatus, the Government immediately forms 15 Implementing Regulations as mandated by the contents of the Final Provisions Article 152 of Law No. 8 of 2016 concerning Disabled Persons, Providing a 10% quota to persons with disabilities to be able to sit in government seats, as a form of affirmative action or positive discrimination. the form of legislation starting from top to bottom for synchronization and harmonization, changing the stigma of people with disabilities into persons with disabilities or disabilities (different abilities), changing the concept of charity based on the concept of rights based.Keywords: Disability, Goverment